Penghulu Institution Credibility and Leadership: Critical Challenges in Administrative Reform - Nor Aman, Nadziatul Shazwani; Mohamed, Ahmad Martadha; Abdul Manaf, Halimah (UUM Press, 2019)
The institution of Penghulu is the oldest and longest in the history of government administration in Malaysia. Since 50 century ago the credibility and leadership of Penghulu is maintain at higher respect of society and government structure. However, the credibility of the institution getting weak due to rapid urbanization, lower entry level requirements and inadequate staffing diminish the power and influence of Penghulu. They are no longer seen as the authoritative figure for rural development, deliver their functions and existence have been questioned. Building upon this framework, this paper attempts to examine the challenges facing by institution of Penghulu in deliver duties in Kedah state administration. The study utilizes a qualitative method that involves personal interviews of 10 currents and former Penghulu as well as former state secretary in Kedah. The findings of the interviews are classified based on three major themes: entry level requirements, human resource development, and symbol of reference.